Epidemiological characteristics of breakthrough mumps infection cases from 2019 to 2023 in Chongqing, China - Yang Liu; Xiaoya Cai; Deming Yang; Yu Xiang; Qing Wang; Ning Yao; Yuanyuan Zhang; Jiawei Xu (Human Vaccines & Immunotherapeutics)
The high coverage of mumps-containing vaccine (MuCV) has effectively controlled the mumps incidence, while the prevention and control of breakthrough cases has become a prominent problem. To analyze the epidemiology of mumps breakthrough cases in Chongqing from 2019 to 2023, and provide scientific evidence for the prevention and control of mumps. The data of clinical and laboratory-confirmed mumps cases in Chongqing from 2019 to 2023 were exported from the China Information System for Disease Control and Prevention. The immunization history was screened and matched from the Chongqing Immunization Program Information System. Least-Significant Difference (LSD) and T-test were used for data analysis. There were 12,566 breakthrough cases in Chongqing, accounting for 61.09% of the total mumps cases reported. The most breakthrough infection occurred in the 3–9 years age group. In 2019 and 2020, the mean age of breakthrough cases with two doses was older than that with one dose (p < .05). In 2022 and 2023, the age was younger than that with one dose (p < .05). The breakthrough intervals for one dose and two doses were (4.87 ± 2.57) and (2.01 ± 1.79) years, respectively. The proportion of breakthrough mumps cases continues to increase in highly vaccinated populations in Chongqing. It is necessary to carry out research on a supplementary dose of MuCV vaccination strategy, and enhance the monitoring of mumps outbreaks in key populations such as children in kindergartens and primary schools.